AKTIVITAS KOLABORASI DAN KEMAMPUAN MENGEMBANGKAN GAGASAN DALAM MENULIS KALIMAT IKLAN PADA PEMBELAJARAN BAHASA INDONESIA DI SMPN 3 CIBINONG KABUPATEN BOGOR - Stella Talitha; Rina Rosdiana; Rini Susilawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2019)
ABSTRACTThis research is based on student collaboration activities and the ability of students to develop ideas in writing advertising sentences. The formulation of the problem in this study is (1) How is the collaborative activity in learning Indonesian at Cibinong 3 Public Junior High School Bogor? (2) What is the result of the ability of students to develop ideas in writing advertising sentences in learning Indonesian at Cibinong 3 Public Junior High School Bogor? This study aims to describe: (1) collaborative activities on learning Indonesian at Bogor Cibinong 3 Junior High School (2) the results of students' ability to develop ideas in writing advertising sentences in Indonesian language learning at Bogor Cibinong 3 Junior High School. The method used in this research is the qualitative method. The results of this study in the form of collaborative activities on learning Indonesian at SMPN 3 Cibinong Bogor are as follows. a) identifying sentences of facts and opinions on products, b) giving ideas about sentences of facts and opinions, c) giving opportunities (taking turns, giving ideas about sentences of facts and opinions), d) discussing the answers of his group friends, e) utilizing time effectively, f) conveying ideas of facts and opinions in accordance with the product, and g) confirming the ideas of sentence facts and opinions recorded to group friends. The results of students' ability to develop ideas in writing ad sentences on learning Indonesian at Bogor Cibinong 3 Junior High School are good. This is based on data on the results of student skills, there are 32 data facts or correct sentences of 82.05% and 34 correct opinion sentence data or equal to 87.18%.Keywords: collaboration activities, advertising sentences, facts, opinions